The Teacher’s Understanding about Problem Based Learning and It’s Implementation - Arum, Rahayu Lailatul; Hikmat, Mauly Halwat (Universitas Negeri Semarang, 2024)
The existence of the curriculum is one of the components that has a strategic role in the education system. Without the right curriculum, students will not get learning targets that are appropriate and tailored to the needs of students in their respective eras. The study is aimed at to describe teachers’ understanding of the Problem Based Learning model in English teaching and to analyze the implementation of the Problem Based Learning model in English teaching at SMP Muhammadiyah 1 Surakarta. The type of research that used in this study was a qualitative approach. From the results of interviews and observational data that researchers conducted, the teacher has implemented the steps of the Problem Based Learning procedure coherently, it’s just that due to lack of time management so that the fourth step cannot be done, and researchers cannot conclude its suitability